2012
DOI: 10.1186/1471-2407-12-170
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening and adherence to follow-up among Hispanic women study protocol: a randomized controlled trial to increase the uptake of cervical cancer screening in Hispanic women

Abstract: BackgroundIn the US, Hispanic women have a higher incidence of, and mortality from, cervical cancer than non-Hispanic white women. The reason for this disparity may be attributable to both low rates of screening and poor adherence to recommended diagnostic follow-up after an abnormal Pap test. The 'Cervical Cancer Screening and Adherence to Follow-up Among Hispanic Women' study is a collaboration between a research institution and community partners made up of members from community based organizations, the Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 15 publications
2
26
0
3
Order By: Relevance
“…25 Specifically, Latinas have cited barriers such as fear, lack of knowledge, scheduling difficulties, and inadequate communication as salient barriers to care. [5][6][7]26 Our findings add to previous research which found that comprehensive patient navigation approaches, such as those that are culturally specific and language concordant, can significantly improve cancer screening rates among multiethnic populations. [5][6][7] Notably, very few women included in our study did not maintain contact with clinical staff.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…25 Specifically, Latinas have cited barriers such as fear, lack of knowledge, scheduling difficulties, and inadequate communication as salient barriers to care. [5][6][7]26 Our findings add to previous research which found that comprehensive patient navigation approaches, such as those that are culturally specific and language concordant, can significantly improve cancer screening rates among multiethnic populations. [5][6][7] Notably, very few women included in our study did not maintain contact with clinical staff.…”
Section: Discussionsupporting
confidence: 69%
“…[5][6][7]26 Our findings add to previous research which found that comprehensive patient navigation approaches, such as those that are culturally specific and language concordant, can significantly improve cancer screening rates among multiethnic populations. [5][6][7] Notably, very few women included in our study did not maintain contact with clinical staff. In addition to language barriers, cultural barriers and Hispanic beliefs surrounding the diagnosis of cancer may contribute to observed lack of care as well.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Increase in adherence to the uptake of Pap smear exam Cervical cancer screening and adherence to follow-up among Hispanic women study protocol: a randomized controlled trial to increase the uptake of cervical cancer screening in Hispanic women (22) 2012/ USA Parallel controlled randomized intervention/600…”
Section: Educational Interventionmentioning
confidence: 99%
“…An interventionist study carried out with 135 Chinese women living in New York City in the United States found that education in health intervention associated with the Internet was efficacious to increase women's adherence to the uptake of Pap smear exams (18) . In this sense, randomized interventionist studies considered educational activities as an efficacious intervention to increase adherence to the uptake of Pap smear exams (19)(20)(21)(22)(23) , as well as women's knowledge about prevention (24)(25)(26) . A meta-analysis of the efficacy of interventions to increase adherence to the uptake of Pap smear exams among women from ethnical minorities in the United States pointed out community-based education as one of the most efficacious methods when allied to improved health services (27) .…”
Section: Educational Activitiesmentioning
confidence: 99%